Exposure to Hyperbaric Oxygen Intensified Vancomycin-Induced Nephrotoxicity in Rats - Sabler, Itay M.; Berkovitch, Matitiahu; Sandbank, Judith; Kozer, Eran; Dagan, Zahi; Goldman, Michael; Bahat, Hilla; Stav, Kobi; Zisman, Amnon; Klin, Baruch; Abu-Kishk, Ibrahim (PloS one, 2016)
It has been suggested that oxidative stress is a potential mechanism for vancomycin-induced nephrotoxicity and hyperbaric oxygen therapy (HBO) has been shown to be effective in treating renal toxicity that has been pharmacologically induced in animal models. The aim of this study was to investigate the effect of HBO therapy on vancomycin-induced nephrotoxicity in rats. The study group comprised 36 Sprague Dawley male rats. We treated 30 with 500 mg/kg of intraperitoneal vancomycin once a day for 7 days. Half of these rats received a daily 1-hour treatment with HBO at 2 Atmospheres (ATM) on the same 7 days and formed the HBO+ group. The other 15 subjects received no HBO treatment (HBO- group). The remaining six rats served as the control group, three received HBO treatments alone and no treatment was administered to the other three rats. Laboratory results were obtained on day 8 and the intervention and control groups were compared. Rats in the HBO+ group gained less weight than the HBO- group (11.6 grams vs 22.6 grams; P = 0,008) and had significantly higher serum blood urea nitrogen (99.6 vs 52.6 mg/dL; P<0.001), serum creatinine (0.42 vs 0.16 mg/dL; P = 0.001) and magnesium (3.6 vs 3.1 mg/dL; P = 0.014). The vancomycin blood levels were also higher in the HBO+ group (27.8 vs 6.7 μg/mL; P = 0.078). There were no pathological kidney changes in the control group. All the kidneys from the treated groups (vancomycin +HBO and vancomycin HBO-) showed moderate to severe histopathological changes with no statistical significance between them. This study demonstrated that exposure to hyperbaric oxygen intensified vancomycin-induced nephrotoxicity in rats.